Research on Business Requirement Analysis and Network Architecture of CDN for Power Grid - Yirong Wang; Sining Wang; Ying Zou; Botao Yu (Dianxin kexue)
During the“Twelfth Five Year Plan”，with the continuous deepening development of the SGCC information s ystem，the number of large management information system of one-1evel deployment continues to increase，wide coverage，1arge number of users，and new technologies such as the software-hardware resource pool and the cloud computing，brings new challenge to the data network. CDN（content delivery network）is a virtual network consists of the node server group distributed in different regions. CDN push/pull the information resources to the network edge，allow customers to access content faster. A profound analysis of the demand for the electric power information business accelerating，power CDN network load requirements，and key technology，was given. Based on the electric power information system architecture and the electric power data network，the electric power CDN network system was put forward，which had two levels network architecture and three layers CDN network storage architecture. The CDN network safety protection requirements were analyzed；the electric power CDN control platform and the electric power CDN test bed were designed and developed.